Adornments of empire: Early Christian dress and the colonial composition of gender - Daniel-Hughes, Carly (Journal for the study of the pseudepigrapha, 2025)
This article considers anti-adornment rhetoric circulating in Roman antiquity and in two of the earliest and most extensive treatments of dress by early Christian writers, namely, treatises by Tertullian of Carthage and Clement of Alexandria. It treats ancient Roman-period discourses of anti-adornment to reveal how configurations of gender were entangled in Roman-imperial race–making and colonial projects. Tertullian’s and Clement’s treatments of adornment, it argues, likewise rehearse Roman colonial imaginaries. Their declamations against luxurious dress and adornment are read here as registering Roman colonial anxieties about the intermingling of populations, the influx of goods and peoples, and the fluctuating dynamics of social belonging and self-display Roman imperial order demanded. It concludes that these Christian authors’ discourse on gendered adornment indicates their investment in and contributions to ancient Roman ethno-racial and imperial formations. Finally, in conversation with Americanist Anne Anlin Cheng’s concept of “ornamentalism,” it offers a brief consideration of how their rhetoric figures in the longue durée of western imaginaries of Asiatic femininity.